Emotional and Sexual Adaptation to Colon Cancer: Perceptual Congruence of Dyadic Coping Among Couples - Stulz, Alexandra; Favez, Nicolas; Flahault, Cécile (Frontiers in Psychology, 2022)
Context: Colon cancer is the 3rd most common cancer in the world. The diagnosis leads the patient and his relatives into a process of mourning for their health and previous life. The literature highlights the impact of the disease on couples. Cancer can either alter or strengthen the relationship. The disease will directly or indirectly affect both partners. Such impact starts with the diagnosis and lasts long after treatments. No study has analysed both emotional and sexual interactions between partners throughout the illness so far. Objective: This research aims to identify and describe whether congruence within couples tends to improve emotional and sexual adjustment. Method: 13 couples took part in this research by answering a set of questionnaires investigating, in particular, dyadic coping strategies, marital and sexual satisfaction. Non-parametric analyses were performed on the quantitative data. Results: Emotional satisfaction is good among the couples in our study. There are important similarities in partners’ emotional adjustment. Patients who are most satisfied with their couple typically have a partner who is also satisfied. This was an expected result based on the literature. Overall, sexual satisfaction is described as average, which is either related to a low frequency of sexual intercourse, or a gap between the ideal and actual frequency of intercourse. In terms of dyadic coping, similarities within couples tend to improve emotional and sexual adjustment. Couples in which communication about stress between the patient and their partner is congruent tend to report good marital satisfaction. We found the same results for delegated coping of both the patient and the partner, and for negative coping of the partner. Sexual adjustment is linked to a similar perception within the couple of a common dyadic coping. Conclusion: Emotional and sexual adjustment is largely linked to the quality of the partner's support. The congruence of couple support strategies has been identified as an important factor in emotional satisfaction. In addition, the more couples implement joint stress management, the better their sexual satisfaction.